PW 0473 Travel behaviours and barriers for transport safety of older adults in sri lanka. (November 2018) - Tennakoon, Varuni; Peiris-John, Roshini; Wickremasinghe, Rajitha; Yasawardene, Surangi; Ameratunga, Shanthi
Abstract : Mobility and social participation greatly enhance the well-being and quality of life of older adults. A rapid increase in older populations together with comorbidities in the process of ageing have important implications for transport policies globally, and especially in low-and-middle-income countries. This study aimed to explore older adults' travel behaviours and challenges for transport safety in Sri Lanka, where the demographic transition and non-communicable disease burden make older people and those living with disability particularly vulnerable to road traffic injury. Utilising registers of Social Services Departments of three Divisional Secretariats in the Colombo district, a random household travel survey recruited 90 older people aged 60 years and above. An interviewer-administered questionnaire explored participants' travel patterns and barriers to safe transportation. Nearly 50% of participants had primary education or less. Almost 80% earned less than Rs. 20 000 (US 130) per month. A total of 80% of participants reported disabilities such as visual impairments (33.3%) and arthritis (33.3%). A 48 hour travel record showed that 73% of participants travelled mainly to community meetings (26% of trips), the majority doing so by foot (37%) or using public buses (36%). Pedestrians reported risks of injury, poor road conditions, and reckless driving as important concerns influencing travel. Public transport users reported unfavourable vehicular designs and services, unavailability of seats, and negative attitudes of service providers as important barriers. Poor public transport systems have resulted in perceived injury risks and related missed opportunities for mobility, delays in getting services, and financial burdens on older adults. The travel patterns, constraints and perceptions reported by older Sri Lankans emphasize the need to implement age and disability friendly road designs and transportation systems alongside increased public awareness of needs of older people. Policy implications based on this knowledge will promote safe transportation and well-being of these communities.